EMIGRATION AS A CIVILIZING FORCE: THE PORTUGUESE IN THE AFRICAN COLONIES AND IN THE INDEPENDENT BRAZIL - Goncalves, Paulo Cesar [UNESP] (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2018)
The analysis of the Geographical Society of Lisbon reports of the parliamentary inquiries on emigration and of studies of some contemporary scholars allows us to focus on the overseas migratory moves, inserting them in the colonialist Portuguese expansion with specific purposes of establishing the empire in Africa between the late 19th century and the early 20th century. The purpose is to investigate the defense of the emigration of Portuguese citizens to the African possessions as an alternative to the colonization process in opposition to the traditional Brazilian destination, with its individual and national economic prospects represented by the remittances.
Keywords: Emigration; colonization; Portuguese colonial Empire; Geographical Society of Lisbon; Brazil